THE IMPACT OF MOTIVATIONAL FACTORS ON TEACHER PERFORMANCE: A LITERATURE REVIEW: THE IMPACT OF MOTIVATIONAL FACTORS ON TEACHER PERFORMANCE: A LITERATURE REVIEW - Fitri, Fitri widya Jayanti Hasibuan; Gustina Permatasari Ritonga1; Sundari Fitri; Miarni Audina (PEBSAS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
This research aims to explore the impact of motivational factors on teacher performance through a comprehensive literature review. Motivation has a central role in shaping individual behavior and performance, especially in the educational context where teachers play a crucial role. This abstract summarizes a synthesis of findings from related literature involving motivational factors and how these factors influence teacher performance. It is hoped that the results of this research will provide in-depth insight into the complexity of the interaction between teacher motivation and performance.